The sample problem: 14(x-4)-(x+2)=(x+2)(x-4)
They transformed this into standard form:
x^2 - 15x + 50 = 0
I have no CLUE as to how they got this. My problem I need to transfer into standard form is:
12(x-4)-(x-2)=(x+2)(x-4)
Can someone please point me in the right direction?
Thanks!
They transformed this into standard form:
x^2 - 15x + 50 = 0
I have no CLUE as to how they got this. My problem I need to transfer into standard form is:
12(x-4)-(x-2)=(x+2)(x-4)
Can someone please point me in the right direction?
Thanks!